Investigating University Level Efl Undergraduate Learners’ Attitudes about Padlet: A Web- Based Digital Tool In Reading Classroom - Usman Shah Toti (University of Chitral Journal of Linguistics and Literature, 2024)
The purpose of this mixed-method research was to assess the attitudes and perceptions of a sample of 21 University level Saudi Undergraduate EFL students at Majma University, Community College towards using Padlet as a collaborative web-based online digital tool in reading classroom. Participants were enrolled in reading introductory course. The research applied by the researcher was basically descriptive in nature and survey method for which students’ oriented set of questionnaire was designed. The questionnaire included 21 items related with respondents’ different categories of variable constructs on 5points likert scale. The research tools used for data collection were semi-structured interviews, researcher’s observation and a questionnaire. Data collected revealed that respondents indicated positive attitudes towards Padlet application in reading classroom. Maximum number of students enjoyed Padlet tool with great zeal. Furthermore, students valued the instructors’ feedback and peer discussion using Padlet.